Reconstructing Well-Being for the Millennial Generation: A Phenomenological Study of Palm Sugar Production in Polewali Mandar - Arwin Arwin; Sulkarnain Sulkarnain; Rezky Amalia Hamka; Sari Hidayati; Aldi Aldi (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Background: The palm sugar sector in Polewali Mandar Regency plays an important role in the local economy, yet there is a declining interest among the millennial generation to work as palm sugar producers. This phenomenon raises concerns about the sustainability of production and rural workforce regeneration. Aims: This study aims to reconstruct the meaning of well-being among millennials who choose not to work as palm sugar producers, and to understand how their subjective interpretations of work influence career decisions in the traditional agricultural sector. Method: A qualitative phenomenological approach was employed, conducted from July to September 2025 in four sub-districts of Polewali Mandar Regency, West Sulawesi, Indonesia. Data were collected through in-depth interviews with seven purposively selected informants, including millennials and elderly palm sugar producers. Data analysis focused on identifying perceptions of well-being, work preferences, and lifestyle aspirations. Findings: The results indicate that for millennials, well-being extends beyond basic economic fulfillment to include financial stability, self-development opportunities, lifestyle flexibility, and work-life balance. Based on Maslow’s hierarchy of needs, they tend to prioritize higher-level needs such as self-actualization and social recognition, rather than merely meeting physiological needs. Traditional palm sugar production is perceived as physically demanding, monotonous, and socially limiting, whereas formal sector jobs are seen as offering prestige, stability, and personal growth. Conclusion: The shifting meaning of well-being among millennials reflects broader value changes that challenge workforce regeneration in traditional agriculture. Local governments and the private sector should diversify employment opportunities and modernize the palm sugar sector to make it more attractive to younger generations.